2005
DOI: 10.1177/104063870501700503
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Feline Caliciviruses Associated with a Hemorrhagic-Like Disease

Abstract: Abstract. Feline calicivirus (FCV) is 1 of the most common causes of upper respiratory tract disease in cats. Other disease syndromes associated with FCV infection have been reported. Recently, calicivirus infection associated with a hemorrhagic-like disease leading to significant mortality in cats has been reported. The clinical signs are similar to those observed with the calicivirus of rabbit hemorrhagic disease. This study characterized 2 FCV isolates associated with hemorrhagic-like disease. Nucleotide se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 40 publications
3
37
0
Order By: Relevance
“…The most widely dispersed lineage (strain L) contained variants of FCV F9, a common strain included in several live attenuated vaccines (4,33). This vaccine virus is occasionally shed by vaccinated individuals (26), and variants of this strain are regularly, albeit occasionally, found in the general cat population (1,6,7,37). As such, the geographical range of this strain is unsurprising and likely represents the widespread use of live F9 vaccines rather than natural virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…The most widely dispersed lineage (strain L) contained variants of FCV F9, a common strain included in several live attenuated vaccines (4,33). This vaccine virus is occasionally shed by vaccinated individuals (26), and variants of this strain are regularly, albeit occasionally, found in the general cat population (1,6,7,37). As such, the geographical range of this strain is unsurprising and likely represents the widespread use of live F9 vaccines rather than natural virus transmission.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the case of feline calicivirus (currently the only member of the species Feline calicivirus ) there are dozens of variants that differ slightly in their genomic sequence. Most of them (the standard poodles) cause a relatively benign disease in domestic cats ( Felis catus ), but a few others (the German shepherds) cause a hemorrhagic fever with high lethality, although their genomic sequences do not differ drastically from those of the less virulent (standard poodle) variants [1, 20, 26, 31]. Clearly, all these viruses are related and belong to the same species––but it is equally clear that these two groups of feline caliciviruses are as different as two different dog breeds, i.e.…”
Section: Explanations For the Current Confusionmentioning
confidence: 99%
“…Feline calicivirus (FCV) is an important pathogen of cats and is commonly associated with upper respiratory tract disease [8]. Other clinical manifestations may include lingual ulcers [23], chronic gingivitis, pharyngitis [31], chronic stomatitis [30], pneumonia [30], acute arthritis [6,21], jaundice with virulent systemic FCV disease and multi-organ failure [1,15,22,27], and death from in utero infection [7]. However, existence of an asymptomatic carrier state is not uncommon, with up to 20-25% of apparently healthy cats shedding the virus [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…The FCV genome has relatively high genetic variability; however, genetic analysis of a variety of isolates from a previous investigation has shown that the first 52 nucleotides in all known sequences are 100% conserved. Nucleotides 101-120 of the genome were also found to be highly conserved among FCV isolates [1,10]. Virus isolation and conventional reverse transcription polymerase chain reaction (RT-PCR) are the most common methods used for FCV diagnosis [9,29].…”
Section: Introductionmentioning
confidence: 99%